Transient start-up of an electric swashplate refrigeration compressor. (September 2021) - Arqam, Mohammad; Dao, Dzung Viet; Mitchell, Mark; Woodfield, Peter
Highlights: An easy to implement transient swashplate compressor model is developed. Mechanism inertia is included to evaluate motor torque loading during start-up. The start-up behaviour is tracked experimentally using a high-speed data logger. Inertia is found to have only a small effect on the compressor torque and power output. Supply lines pressure are found to have the largest influence on the staring torque. Abstract: The design of compact, high performance electric swashplate refrigeration compressors demands a clear understanding of different physical phenomena and their interactions taking place inside the compressor. The dynamic characteristics of the compressor are associated with the start-up transients of the swash-plate mechanism and the time variation of suction and discharge pressures. An experimentally validated, easy to implement transient swashplate compressor model has been developed that can capture the essential physics, including inertia of the pistons and swashplate to evaluate the electric motor torque loading during compressor start-up. The effects of moment of inertia, bearing torque, viscous resistance to piston motion, and suction and discharge pressures on the torque and compressor mechanical input power are investigated. For model validation, the start-up behavior is tracked experimentally using a high-speed data logger to monitor the changing phase currents of the brushless DC motor, capturing both the instantaneous power and rotational speed. Rotational mass moment of inertia is found to have only a small effect on the compressor torque and power output and can be made negligible by changing settings in the start-up algorithm for the electric motor controller. Suction and discharge pressures during start-up are found to have the largest influence on the required starting torque. More than 95% of torque is found to be because of the line pressures. Predictions are in good agreement with measurements and show that depending on the starting refrigerant pressures in the supply lines, the starting torque can be lower than the operating torque for the compressor. The original contribution of this work is in deriving a transient swash-plate compressor model that includes the inertia of the swash-plate mechanism and in clarifying the relative importance of inertia, line pressures, viscous losses and bearing resistance on the required start-up torque for this type of compressor.